BETWEEN POWER AND COOPERATION: A REALISM-LIBERALISM STUDY OF INDONESIA'S BRICS MEMBERSHIP IN A MULTIPOLAR WORLD - Firman Prima Laras (Budi Luhur Journal of Strategic & Global Studies, 2025)
Abstract: This study analyzes the dynamics of discourse, motivations, and Indonesia's decision to join BRICS, using the lenses of realism and liberalism in international relations.The realist perspective views Indonesia’s move as an effort to strengthen its bargaining position amid great power rivalries, diversify export markets, and secure strategic resources, as reflected in the dominance of non-oil and gas exports to China and India based on BPS 2023 data. The liberal perspective emphasizes the opportunities to expand multilateral cooperation, promote South-South solidarity, and access development financing through the New Development Bank. This research employs a qualitative document-based method, triangulating trade data, official government statements, media reports, and international relations literature (Kaufman, 2022; Stuenkel, 2020; Kauppi & Viotti, 2020; Nau, 2019). The findings indicate that Indonesia integrates both realist and liberal approaches in considering its BRICS membership: realist power calculations are manifested through strategic partner diversification, while liberal aspirations are reflected in the commitment to strengthening Global South cooperation. Indonesia’s decision to join BRICS reflects a cautious strategic approach, weighing economic-political benefits while upholding the "free and active" foreign policy principle. This study underscores the importance of balancing national interests and multilateral commitments in shaping Indonesia’s foreign policy in a multipolar era.   Abstrak: Studi ini menganalisis dinamika wacana, motivasi, dan keputusan Indonesia untuk bergabung dengan BRICS., menggunakan lensa teori realisme dan liberalisme dalam hubungan internasional. Perspektif realisme memandang langkah Indonesia sebagai upaya memperkuat posisi tawar di tengah rivalitas kekuatan besar, mendiversifikasi pasar ekspor, dan mengamankan sumber daya strategis, tercermin dari dominasi ekspor nonmigas ke Tiongkok dan India berdasarkan data BPS 2023. Perspektif liberalisme menyoroti peluang memperluas kerjasama multilateral, solidaritas Selatan-Selatan, dan akses terhadap pembiayaan pembangunan melalui New Development Bank. Penelitian ini menggunakan metode kualitatif berbasis dokumen dengan analisis triangulasi terhadap data perdagangan, pernyataan resmi pemerintah, laporan media, dan literatur teori hubungan internasional (Kaufman 2022; Stuenkel 2020; Kauppi and Viotti 2020; Nau 2019). Hasil penelitian menunjukkan bahwa Indonesia memadukan pendekatan realis dan liberal dalam mempertimbangkan keanggotaan BRICS: kalkulasi kekuatan realistis diwujudkan melalui diversifikasi mitra strategis, sementara aspirasi liberal tercermin dalam komitmen memperkuat kerjasama global Selatan. Keputusan Indonesia untuk bergabung dengan BRICS mencerminkan kehati-hatian strategis dalam menimbang manfaat ekonomi-politik, sekaligus menjaga prinsip kebijakan luar negeri “bebas aktif”. Temuan studi ini menekankan pentingnya keseimbangan antara kepentingan nasional dan komitmen multilateral dalam merumuskan kebijakan luar negeri Indonesia di era multipolar.